Sesquiterpene lactones from Gynoxys verrucosa and their anti-MRSA activity - Malagon Aviles, O. (2011)
Ethnopharmacological relevance: Because of its virulence and antibiotic resistance, Staphylococcus aureus is a more formidable pathogen now than at any time since the pre-antibiotic era. In an effort to identify and develop novel antimicrobial agents with activity against this pathogen, we have examined Gynoxys verrucosa Wedd (Asteraceae), an herb used in traditional medicine in southern Ecuador for the treatment and healing of wounds. Materials and methods: The sesquiterpene lactones leucodine (1) and dehydroleucodine (2) were extracted and purified from the aerial parts of Gynoxys verrucosa, and their structure was elucidated by spectroscopic methods and single-crystal X-ray analysis. The in vitro anti-microbial activity of Gynoxys verrucosa extracts and its purified constituents was determined against six clinical isolates including Staphylococcus aureus and Staphylococcus epidermidis strains with different drug-resistance profiles, using the microtiter broth method. Results: Compound 1 has very low activity, while compound 2 has moderate activity with MIC 50s between 49 and 195 ?g/mL. The extract of Gynoxys verrucosa has weak activity with MIC 50s between 908 and 3290 ?g/mL. Conclusions: We are reporting the full assignment of the 1H NMR and 13C NMR of both compounds, and the crystal structure of compound 2, for the first time. Moreover, the fact that compound 2 has antimicrobial activity and compound 1 does not, demonstrates that the exocyclic conjugated methylene in the lactone ring is essential for the antimicrobial activity of these sesquiterpene lactones. However, the weak activity observed for the plant extracts, does not explain the use of Gynoxys verrucosa in traditional medicine for the treatment of wounds and skin infections. © 2011 Elsevier Ireland Ltd. All rights reserved.